Citizen Journalism in Cyber Media: Protection and Legal Responsibility Under Indonesian Press Law - Prahassacitta, Vidya (Humaniora, 2017)
Phenomena of citizen journalism had accepted and become part of cyber media. Cyber media owned and managed by press companies had featured citizen journalists? information, critics, opinions, and news. Citizen journalism was part of freedom of expression. However, in Indonesia?s press law concept, it was not part of the national press. This created legal issues regarding protection and legal responsibility aspects for both parties. A qualitative research was conducting to solving these issues. Using secondary data from literature study and observation on several cyber media websites, this discovers two conclusions. First, the citizen journalist is part of freedom of the press; it means that a citizen journalist?s creation has protected form censor and bans. However, a citizen journalist still has a limitation which shall be complied videlicet Civil Code and Law No. 11 The year 2008 concerning Information and Electronic Transaction. Violation of both regulations means that a citizen journalist shall be legally responsible. Second, protection and responsibility border between a citizen journalist and press company are based on an agreement. Approval of term and condition of general user content in a website from a citizen journalist means that both parties have agreed to enter into an agreement. A press company might be freed of its legal responsibility as long as conducted its obligation to control and manage contents that have been uploaded and published by a citizen journalist. If the company does not take proportional action against citizen journalist? contents that violating the law, the press company shall be requested its civil or criminal legal responsibility.